Formulation Development and Evaluation of Clopidogrel Fast Dissolving Tablets: Clopidogrel fast dissolving tablets - Gunda Raghavendra Kumar; J.N.Suresh Kumar; V.Satyanarayana; G.Swarupa Rani; B.Satya Prasad (Iranian Journal of Pharmaceutical Sciences, 2016)
The main objective of the present research work is to formulate the Clopidogrel Fast Dissolving tablets. Clopidogrel, an antiplatelet drug, belongs to BCS Class-II and used to control Heart attack, Hypertension by inhibiting Platelet activation and aggregation .The Fast Dissolving tablets of Clopidogrel were prepared employing different concentrations of Crospovidone and Croscarmellose sodium in different combinations as a Superdisintegrant by Direct Compression technique using 32 factorial design. The concentration of Crospovidone and Croscarmellose sodium was selected as independent variables, X1 and X2 respectively whereas, wetting time, Disintegration time, t50%, t90% were selected as dependent variables. Totally nine formulations were designed and evaluated for hardness, friability, thickness, Assay, Wetting time, Disintegration time, and in-vitro drug release. From the Results it was concluded that all the formulation were found to be with in the Pharmacopoeial limits and the in-vitro dissolution profiles of all formulations were fitted into different Kinetic models, the statistical parameters like intercept (a), slope (b) and regression coefficient (r) were calculated. Polynomial equations were developed for Wetting time, Disintegration time, t50%, t90%. Validity of developed polynomial equations was verified by designing 2 check point formulations (C1, C2). According to SUPAC guidelines, the formulation (F5) containing combination of 15% Crospovidone and 15% Croscarmellose, is the most similar formulation (similarity factor f2=91.3936, dissimilarity factor f1= 1.203& No significant difference, t= -0.00062) to marketed product (PLAVIX-75). The selected formulation (F1) follows First order, Higuchi’s kinetics, mechanism of drug release found to be Fickian Diffusion (n= 0.226).